Who’s Who of World Religions
XVI, 560 p.
Keywords: In historical terms, religions do not exist apart from the people who practise them. This is the first collection of biographical studies of figures from religions around the globe and from traditions both ancient and modern. It represents the work of an enormous international team of scholars, and although many entries involve original research, this substantial work of reference is intended to be of use to both the specialist and the general reader. Particular care has been taken to ensure a balance between religions and to include figures from the diverse branches of the different religions. Indexes and an extensive bibliography make it an invaluable working tool.